Mutations in the VP1 coding region of polyomavirus determine differentiating stage specificity. - Ricci, L (1992)
Polyomavirus mutants capable of replicating in undifferentiated murine C2 myoblasts were selected and characterized. These mutants grow normally in 3T6 mouse fibroblast cells, and they do not complement the wild-type virus in coinfection experiments of C2 myoblasts. Of 12 isolates, 10 possess duplications of the regulatory region including the enhancer A domain. On the bases of the regulatory region structure and the presence and length of the enhancer duplication, the mutant viruses could be grouped into three classes. One mutant class (e.g., PyMB3) possesses an enhancer duplication of 91 bp identical to that of a previously characterized polyomavirus mutant, PyNB11/1. We have demonstrated that this enhancer duplication gives rise at its junction to a novel recognition motif for the transcriptional factor NF-1 (M. Caruso, C. Iacobini, C. Passananti, A. Felsani, and P. Amati, EMBO J. 9:947-955, 1990). The regulatory region PyMB3 virus recombined in a wild-type genome context maintains the mutant phenotype. The other two types of mutants, one with a 30-bp enhancer duplication (e.g., PyMB40) and one with a wild-type enhancer structure (e.g., PyMB27), possess two similar but distinct 6-bp deletions in the same region of the VP1 coding gene. In both cases, the ability to replicate in undifferentiated C2 myoblasts is strictly correlated to the mutation in the VP1 coding region.